Toward a Reasoned Classification of Diseases Using Physico-Chemical Based Phenotypes - Schwartz, Laurent; Lafitte, Olivier; da Veiga Moreira, Jorgelindo (Frontiers in Physiology, 2018)
Background: Diseases and health conditions have been classified according to anatomical site, etiological and clinical criteria. Physico-chemical mechanisms underlying the biology of diseases, such as the flow of energy through cells and tissues, have been often overlooked in classification systems. Objective: We propose a conceptual framework towards the development of an energy-oriented classification of diseases, based on the principles of physical-chemistry. Methods: A review of literature on the physical-chemistry of biological interactions in a number of diseases is traced from the point of view of the fluid and solid mechanics, electricity, and chemistry. Results: We found consistent evidence in literature of decreased or/and increased physical and chemical forces intertwined with biological processes of numerous diseases, which allowed the identification of mechanical, electric and chemical phenotypes of diseases. Discussion: Biological mechanisms of diseases need to be evaluated and integrated into more comprehensive theories that should account with principles of physics and chemistry. A hypothetical model is proposed relating the natural history of diseases to mechanical stress, electric field and chemical equilibria (ATP) changes. The present perspective towards an innovative disease classification may improve drug-repurposing strategies in the future.